Internet filtering trends in liberal democracies: French and German regulatory debates - Joss Wright; Yana Breindl (Internet Policy Review, 2013)
Liberal democracies are increasingly considering internet filtering as a means to assert state control over online information exchanges. A variety of filtering techniques have been implemented in Western states to prevent access to certain content deemed harmful. This development poses a series of democratic and ethical questions, particularly when states introduce regulation mandating internet service providers to block online content. In this article we examine the debates surrounding filtering that have played out in two key European states, France and Germany, focusing on the arguments used by opponents and proponents of internet blocking. We use these to explain and analyse the outcomes of both cases and, more broadly, the various challenges posed by internet blocking to democracy.